Paraquat genotoxicity in mammalian cells: the role of DNA repair in induced mutation - Gunselman, Sandra J., author; Waldren, Charles A., advisor; Slaga, Thomas J., committee member; Gardner, Henry S., committee member; LaRue, Susan M., committee member (Colorado State University. Libraries, 2001)
Paraquat (1.1--dimethyl-4. 4--bipyridinium, PQ) is an herbicide, which poses serious human health concerns where it is in widespread use. It is the leading cause of accidental death in some parts of the world including Taiwan and Thailand. The United States Environmental Protection Agency (EPA) has classified PQ as a toxin and weak carcinogen. PQ is redox-cycled in cells producing reactive oxygen species (ROS) and causing lipid peroxidation, gene inactivation and DNA damage. PQ has been reported to cause chromosomal aberrations in cells however, until recently, it has been considered non-mutagenic. The genotoxicity of PQ was studied using the human x Chinese hamster ovary (CHO) cell line, ALH. These cells contain a single copy of human chromosome 11 and express the surface cell antigen CD59. New variants of ALH were also created which expressed the E. coli fpg gene. This gene encodes for the base excision repair protein, formamidopyrimidine glycosylase (FPG), and by transfecting it into the ALH cell line, cells with increased DNA repair capacity were produced. Mutations induced by PQ were measured in both cell types at the CD59 locus. FPG activity was measured in ALH and fpg transformant cells and compared with survival and induced mutation data following PQ exposure. Protein extracts from a number of the fpg transformants were found to more efficiently excise 8oxoG, the major damage caused by oxidation in the cell, than ALH cells. One of the transformants that displayed effective excision was found to have increased survival when compared to ALH cells and induced mutation was virtually eliminated - clear evidence that PQ causes mutagenic DNA damage in mammalian cells. Results of this study demonstrate, for the first time, that PQ is an effective mutagen in mammalian cells and that its mutagenicity is abrogated by the activity of the bacterial fpg gene. These results offer important insight into the role DNA repair plays in preventing mutagenic changes caused by oxidizing reagents. Cells possessing an impaired or non-functioning repair enzyme system would likely build up mutagenic changes in their genome, increasing genomic instability and placing them at heightened risk for oxidatively-induced disease.
Keywords: molecular biology; cellular biology